DIMP53‐1: a novel small‐molecule dual inhibitor of p53–MDM2/X interactions with multifunctional p53‐dependent anticancer properties. Issue 6 (2nd May 2017) - Soares, Joana; Espadinha, Margarida; Raimundo, Liliana; Ramos, Helena; Gomes, Ana Sara; Gomes, Sara; Loureiro, Joana B.; Inga, Alberto; Reis, Flávio; Gomes, Célia; Santos, Maria M. M.; Saraiva, Lucília
Abstract : The transcription factor p53 plays a crucial role in cancer development and dissemination, and thus, p53‐targeted therapies are among the most encouraging anticancer strategies. In human cancers with wild‐type (wt) p53, its inactivation by interaction with murine double minute (MDM)2 and MDMX is a common event. Simultaneous inhibition of the p53 interaction with both MDMs is crucial to restore the tumor suppressor activity of p53. Here, we describe the synthesis of the new tryptophanol‐derived oxazoloisoindolinone DIMP53‐1 and identify its activity as a dual inhibitor of the p53–MDM2/X interactions using a yeast‐based assay. DIMP53‐1 caused growth inhibition, mediated by p53 stabilization and upregulation of p53 transcriptional targets involved in cell cycle arrest and apoptosis, in wt p53‐expressing tumor cells, including MDM2‐ or MDMX‐overexpressing cells. Importantly, DIMP53‐1 inhibits the p53–MDM2/X interactions by potentially binding to p53, in human colon adenocarcinoma HCT116 cells. DIMP53‐1 also inhibited the migration and invasion of HCT116 cells, and the migration and tube formation of HMVEC‐D endothelial cells. Notably, in human tumor xenograft mice models, DIMP53‐1 showed a p53‐dependent antitumor activity through induction of apoptosis and inhibition of proliferation and angiogenesis. Finally, no genotoxicity or undesirable toxic effects were observed with DIMP53‐1. In conclusion, DIMP53‐1 is a novel p53 activator, which potentially binds to p53 inhibiting its interaction with MDM2 and MDMX. Although target‐directed, DIMP53‐1 has a multifunctional activity, targeting major hallmarks of cancer through its antiproliferative, proapoptotic, antiangiogenic, anti‐invasive, and antimigratory properties. DIMP53‐1 is a promising anticancer drug candidate and an encouraging starting point to develop improved derivatives for clinical application. Abstract : The novel small‐molecule DIMP53‐1 potentially binds to p53, inhibiting its interaction with MDM2 and MDMX and thus restoring the activity of this tumor suppressor. DIMP53‐1 has in vitro and in vivo p53‐dependent antitumor properties, and no genotoxicity and undesirable toxic effects were observed. DIMP53‐1 is a multifunctional drug targeting major hallmarks of cancer.